Adaptive Robust Control of Variable Speed Wind Turbine Generator - Ahmad Zare; Ahmad Forouzantabar (Institute of Advanced Engineering and Science, 2015)
In this work we want to propose a control strategy to maximize the wind energy captured in a variable speed wind turbines, for this goal the speed of turbine should keep in optimum speed when the wind speed is changing. Many control approach has been suggested that is base on approximate models that it causes unsuitable behavior of system because of Uncertainty parameters of the system. Hence at this work we use adaptive robust control approach that it can to compensate Uncertain of the parameters and present a smooth system with maximum energy production. Numerical simulations are given to illustrate the effectiveness and validity of the proposed approach.